2018
DOI: 10.1186/s13075-018-1746-1
|View full text |Cite
|
Sign up to set email alerts
|

Risk of chronic kidney disease in patients with gout and the impact of urate lowering therapy: a population-based cohort study

Abstract: BackgroundAn association between gout and renal disease is well-recognised but few studies have examined whether gout is a risk factor for subsequent chronic kidney disease (CKD). Additionally, the impact of urate-lowering therapy (ULT) on development of CKD in gout is unclear. The objective of this study was to quantify the risk of CKD stage ≥ 3 in people with gout and the impact of ULT.MethodsThis was a retrospective cohort study using data from the Clinical Practice Research Datalink (CPRD). Patients with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 45 publications
(51 reference statements)
1
39
0
2
Order By: Relevance
“…Our findings are applicable to patients with gout, in whom there is a high prevalence of comorbid heart disease [30][31][32][33] and chronic kidney disease. [34][35][36] In light of the US Food and Drug Administration's warning 2 regarding potential cardiovascular adverse effects related to febuxostat, 37 allopurinol use among patients receiving treatment for gout who also have chronic kidney disease and heart disease may be set to increase. These findings may also have implications for clinical trials of allopurinol among at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are applicable to patients with gout, in whom there is a high prevalence of comorbid heart disease [30][31][32][33] and chronic kidney disease. [34][35][36] In light of the US Food and Drug Administration's warning 2 regarding potential cardiovascular adverse effects related to febuxostat, 37 allopurinol use among patients receiving treatment for gout who also have chronic kidney disease and heart disease may be set to increase. These findings may also have implications for clinical trials of allopurinol among at-risk populations.…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review and meta-analysis involving 190,000 patients revealed that there was a significant positive association between hyperuricaemia and new onset of CKD (OR 2.35) (Ling Li, 2014). Another population-based retrospective cohort study in the UK demonstrated that gout was associated with an increased incidence of CKD especially those who were exposed to urate lowering agent (Matthew Roughley, 2018). They also have higher prevalence of diabetes mellitus, hypertension, and vascular disease which also highly correlated with CKD, and received more NSAIDs than patient without gout (Matthew Roughley, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Another population-based retrospective cohort study in the UK demonstrated that gout was associated with an increased incidence of CKD especially those who were exposed to urate lowering agent (Matthew Roughley, 2018). They also have higher prevalence of diabetes mellitus, hypertension, and vascular disease which also highly correlated with CKD, and received more NSAIDs than patient without gout (Matthew Roughley, 2018). Hence, patient with gout like our patient should be suspected to have CKD, and they should be advised to be cautious on taking NSAIDs during Ramadan fasting to avoid acute deterioration of kidney function.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that chronically high levels of uric acid in the blood could significantly increase the risk of kidney disease [31], and 5.6% of 13338 participants(mean serum uric acid = 5.9 ± 1.5 mg/dL) had incident kidney disease defined by GFR decrease of more than 30% over 8.5 years [32]. Another population-based cohort study showed that patients with CGA who were treated with urate-lowering therapy (ULT) had a greater risk of incident chronic kidney disease (CKD) [33]. Therefore, BUN and creatinine could be regarded as IRFs for the progression of GA, and the significant rising of BUN and creatinine indicates that the course of GA has entered the CGA stage.…”
Section: Discussionmentioning
confidence: 99%